2018
DOI: 10.5505/deutfd.2018.49469
|View full text |Cite
|
Sign up to set email alerts
|

Functional restriction and satisfaction with prosthesis in lower limb amputee patients

Abstract: Bu çalışmanın amacı; alt ekstremite ampute hastalarda fonksiyonel kısıtlılığı ve protez memnuniyetini değerlendirmek ve ilişkili faktörleri ortaya koymaktır. Gereç ve Yöntem: Çalışmaya alt ekstremite ampütasyonu geçirmiş olan 43 hasta alındı. Hastaların demografik ve klinik özellikleri kaydedildi. Hastaların fonksiyonel kısıtlılığını değerlendirmek amacıyla Groningen Aktivite Kısıtlılık Skalası (GARS) kullanıldı. Hasta memnuniyetini belirlemek için ise Protez Memnuniyet Anketi uygulandı. Bulgular: Hastaların y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Kark and Simmons [14] reported this rate as 80.1%. Engin et al [22] reported that 83% of their patients were satisfied with the prosthesis in general. In our study, the average overall prosthesis satisfaction rate was 63.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Kark and Simmons [14] reported this rate as 80.1%. Engin et al [22] reported that 83% of their patients were satisfied with the prosthesis in general. In our study, the average overall prosthesis satisfaction rate was 63.1%.…”
Section: Discussionmentioning
confidence: 99%